2021
DOI: 10.1002/prp2.814
|View full text |Cite
|
Sign up to set email alerts
|

Ocular safety of repeated intravitreal injections of Carboplatin and Digoxin: A preclinical study on the healthy rabbits

Abstract: To evaluate the ocular safety of intravitreal carboplatin and digoxin injections as a new intravitreal chemotherapy option for retinoblastoma tumor vitreous seeds. Eighteen rabbits were divided randomly into three groups to receive intravitreal injection of Digoxin (6 rabbits), Carboplatin (7 rabbits), or Saline (5 rabbits). In every group, one eye randomly treated with 10 µg Digoxin in 0.1 cc or 1 µg Carboplatin or Saline, and the contralateral eye was considered as the control. All groups underwent three con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…It was speculated that the molecular type and structure of conbercept were related to its effects on the fellow eye. Khodabande et al (2021) found some electroretinography changes in contralateral rabbits’ eyes in the unilateral intravitreal injection of digoxin and carboplatin. They proposed it might be related to the repeated intravitreal injection of the agents that cause damage to the ocular-blood barrier.…”
Section: Discussionmentioning
confidence: 90%
“…It was speculated that the molecular type and structure of conbercept were related to its effects on the fellow eye. Khodabande et al (2021) found some electroretinography changes in contralateral rabbits’ eyes in the unilateral intravitreal injection of digoxin and carboplatin. They proposed it might be related to the repeated intravitreal injection of the agents that cause damage to the ocular-blood barrier.…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, OAC may not be the optimal route for digoxin due to low intravitreal levels and systemic exposure related to cardiotoxicity; IVi may be preferable. In rabbits, IVi of digoxin resulted in levels well above the IC 50 and plasma concentrations far below the concentrations related to cardiac toxicity in humans; however, the injected dose was toxic to the retina (110,111).…”
Section: Drug Discovery In Retinoblastomamentioning
confidence: 89%
“…While an effective research tool, safely translating the cardiac glycoside digoxin to patients with ocular disease has proven to be challenging due in part to its complex pharmacokinetic profile and narrow therapeutic index ( 39 ). Indeed, intraocular administration of digoxin in rabbits at therapeutic doses has been reported to result in retinal toxicity ( 51 , 52 ). Similar observations were made following intraocular administration of the chemotherapeutic agent doxorubicin ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%